Contemporary Spiritualities Social and Religious Contexts - Erricker, Clive; Erricker, Jane (London Continuum, 2001)
Spirituality can be understood within both a religious and secular context. Fuelled by the controversy that surrounds different understandings of human identity and notions of progress, knowledge and truth in modernist and postmodernist contexts, the concept of spirituality is a hotly contested topic of debate as to its relevance within contemporary culture and its meaning within religious traditions. This book aims to inform readers on this debate and contextualize it within these different frames of reference. It approaches the topic of spirituality with an identification of the major influe.
Keywords: Religion and sociology. Spirituality. Sociologie religieuse. Spiritualité RELIGION -- Spirituality